2014
DOI: 10.1364/oe.22.031496
|View full text |Cite
|
Sign up to set email alerts
|

Shaping and spatiotemporal characterization of sub-10-fs pulses focused by a high-NA objective

Abstract: We describe a setup consisting of a 4f pulse shaper and a microscope with a high-NA objective lens and discuss the aspects most relevant for an undistorted spatiotemporal profile of the focused beam. We demonstrate shaper-assisted pulse compression in focus to a sub-10-fs duration using phase-resolved interferometric spectral modulation (PRISM). We introduce a nanostructure-based method for sub-diffraction spatiotemporal characterization of strongly focused pulses. The distortions caused by optical aberrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…We then utilize the algorithm presented in Ref. 75 Linearly polarized light, acting as a superposition of left-and right-handed circularly polarized light, is used to simultaneously excite both the transitions in the K and K' valleys.…”
Section: Resultsmentioning
confidence: 99%
“…We then utilize the algorithm presented in Ref. 75 Linearly polarized light, acting as a superposition of left-and right-handed circularly polarized light, is used to simultaneously excite both the transitions in the K and K' valleys.…”
Section: Resultsmentioning
confidence: 99%
“… 17 , 18 Application of sophisticated pulse-shaping techniques have recently shown that it is possible to combine ultrashort near-IR pulses (∼800 nm, sub-10 fs), which have become ubiquitous in ultrafast spectroscopy, with high spatial resolution provided by high numerical aperture (NA) objectives. 37 The extension toward the visible spectral region, where many of the most studied materials are strongly active, however, has been lacking.…”
mentioning
confidence: 99%
“…In case of spatially distorted mode profiles, other techniques that are based on nanoscale probes, not directly relying on the mode profile, can be used (see e.g.Refs. 22,32).At the same time, the graphene four-wave mixing is an extremely efficient process leading to easily detectable signals reaching photon count rates of several millions per second. Most importantly, its spectrally uniform response should allow for phase characterization of laser pulses reaching from the THz to the visible regime.Near-degenerate FWM avoids drawbacks of schemes relying on higher harmonic detection and the associated requirements regarding the achromaticity and the large spectral detection range as discussed in the following.…”
mentioning
confidence: 99%